(untitled) (Journal of Plant Disease Sciences, 2025)
Alternaria brassicae, the causal agent of Alternaria leaf spot in cabbage, is one of the most economically significant and widespread diseases in India and worldwide. Since disease progression is highly dependent on weather conditions, a weather-based forewarning system can help farmers implement timely protective measures. A field experiment was conducted during 2023-24 at the Department of Plant Pathology, College of Agriculture, VNMKV, Parbhani, Maharashtra, to assess the influence of weather parameters on the initiation and spread of Alternaria leaf spot in cabbage. The study also aimed to develop a suitable weather-based disease forewarning equation.